Fishery Harbor Needs Analysis for Fishery Vessel Activities in Ocean Bungus Fishery, West Sumatra Province - Azandy Bamesyah; Nofrizal Nofrizal; Arthur Brown (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The size of the harbor pool will affect the number of ships that will dock. The purpose of this research is to determine the size of the port pool needs and determine the depth of the port pool needed for smooth activities at PPS Bungus. Data collection is done directly in the field to see the maximum number of ships anchored the port pool area (m2), the depth of the port pool (m), data on the width, length, and depth of the largest ship (m), the maximum tide in the port pool (m), and the squat or height of the oncoming ship (m). The results concluded that the existing harbor pool is no longer able to accommodate all ships that dock. The current harbor pool area is 40,000 m2 with 348 vessels, requiring a pool area of 458,762.06 m2. The current average harbor pool depth is 2.75 m, and it is safe for ships to anchor in the harbor pool